Basic Concepts of Community Social Change: A Descriptive Study - Prayogi, Arditya; Diniyanto, Ayon; Prasetya, Dimas (Lentera Ilmu Nusantara, 2024)
Changes that occur in human life in society can be understood as social change. This social change is absolute because it will be experienced by every society wherever and whenever. This article was written with the aim of elaborating on various important things and highlighting several main concepts in social change in society. This is so that the phenomenon of social change in society can be understood more fully. This article was written using a qualitative descriptive method by describing important concepts which are the main points in this article. Data collection is supported by using literature study techniques. From the results of the study, we get a picture that social change as a process of change that occurs in social life always takes place without stopping and will continue along with human existence itself. As a process, social change in a society is not an outcome or finished product. There is a process of mutual agreement or decision taken by each individual or community group. Various agreements in social change in society can be regarding social values, social norms, patterns of organizational behavior, the structure of social institutions, layers in society, power and authority, social interactions and soon.